2011
DOI: 10.1136/amiajnl-2011-000187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computerized surveillance and manual chart review for adverse events

Abstract: The effect that information source has on different surveillance methods depends on the type of AE. Integrating information from physician narratives with CSS using natural language processing would improve the detection of ADEs more than HAIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 30 publications
3
49
0
1
Order By: Relevance
“…More recently, Tinoco and colleagues reported that a computerised surveillance system detected more hospital acquired infections than trigger tool based screening, but a similar number of ADEs 19. Importantly, the study found that only 26% of hospital acquired infections and 3% of ADEs were detected by both methods 19. Our study provides additional support that computer facilitated screening may complement the traditional trigger tool approach and suggests that the rate of hospital AEs may be even higher than previously reported.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…More recently, Tinoco and colleagues reported that a computerised surveillance system detected more hospital acquired infections than trigger tool based screening, but a similar number of ADEs 19. Importantly, the study found that only 26% of hospital acquired infections and 3% of ADEs were detected by both methods 19. Our study provides additional support that computer facilitated screening may complement the traditional trigger tool approach and suggests that the rate of hospital AEs may be even higher than previously reported.…”
Section: Discussionsupporting
confidence: 70%
“…In a study focusing on ADEs, Jha and colleagues reported that a computer based method detected 45% of events, trigger tool based screening detected 65% and only 12% were detected by both methods 14. More recently, Tinoco and colleagues reported that a computerised surveillance system detected more hospital acquired infections than trigger tool based screening, but a similar number of ADEs 19. Importantly, the study found that only 26% of hospital acquired infections and 3% of ADEs were detected by both methods 19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, most studies sought to establish harm rates for benchmarking purposes over large populations with suggestions that between 3% and 17% of patients experience an AE during a hospital admission 22. Most of these studies used retrospective, unstructured case note reviews which are labour-intensive, costly and impractical for the routine monitoring of harm 23. Trigger tool methodology is accepted as one of the ways to measure harm in a way that allows local learning,1 3 2 Trigger tools have also been reported to provide consistent, reliable and relevant data at low cost,2 3 although the cost may vary between different hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…In research, manual chart review is often still considered the “gold standard,” 812 though this method is time consuming and expensive and thus can only be applied to small numbers of patients. As electronic systems matured, administrative health insurance claims were increasingly used to capture information on larger populations.…”
Section: Introductionmentioning
confidence: 99%